PERAN ORANG TUA DALAM MELESTARIKAN BAHASA PANCANA DI KELURAHAN LAKUDO - Muhammad Hidayatullah (KAREBA : Jurnal Ilmu Komunikasi, 2021)
This study aims to analyze the role of parents in preserving the Pancana language and analyze the factors that are the obstacles of parents in preserving the Pancana language in Lakudo Village. The method used in this research is descriptive qualitative method. The data source in this study was obtained from the community in the Lakudo Village, namely three Lakudo people who have the status of family heads and use the Pancana language actively. This research was conducted by interview using the recording technique and note-taking technique. The results of this study are the role of parents in preserving the Pancana language has a positive influence on children in knowing the Pancana language. Some factors that become obstacles for parents in preserving Pancana language are environmental factors and the absence of a place for children to use Pancana so that their interest in using Pancana is reduced.